Analisis Pengendalian Kualitas Olahan Produk Cokelat Rapoviaka Simple Dengan Total Quality Control (TQC) - Dika Rahmatiana; Asngadi Asngadi; Sulaeman Miru; Wiri Wirastuti (Journal Economic Excellence Ibnu Sina, 2024)
The aim of this research was to determine the quality control analysis of processed Rapoviaka Simple chocolate products with total quality control (tqc). The research was carried out through direct observation of all stages of rapoviaka chocolate production, starting from selecting raw materials to the final packaging process. Quality data is obtained through measuring various parameters such as texture, taste, aroma and visual appearance of the product. Quality control analysis is carried out using statistical tools in the form of check sheets, histograms, Pareto diagrams, control maps c. The research results show that the implementation of TQC is effective in improving product quality. After carrying out analysis using the Simple Rapoviaka Chocolate C Control Map, it can be said to be under statistical control. This is because the defect proportion (CL) value is within the expected range, between the specified UCL (Upper Control Limit) and LCL (Lower Control Limit). In other words, the Rapoviaka Simple chocolate production process is within the established statistical control limits. By paying attention to each stage of production and implementing strict quality controls, variability in products can be reduced significantly. This research provides an important contribution in the context of developing a quality control system in the food industry, especially for processed chocolate products.